2001
DOI: 10.1115/1.1408938
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Hemodynamics After “Edge-to-Edge” Mitral Valve Repair

Abstract: Edge-to-edge mitral valve repair consists in suturing the free edge of the leaflets to re-establish coaptation in prolapsing valves. The leaflets are frequently sutured at the middle and a double orifice valve is created. In order to study the hemodynamic implications, a parametric model of the left heart has been developed. Different valve areas and shapes have been investigated. Results show that the simplified Bernoulli formula provides a good estimation of the pressure drop and that the pressure drop may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…Clinically, others have shown that even with concomitant ring annuloplasty, the edge-to-edge technique does not cause mitral valve obstruction, either at baseline or during physical exercise, and does not affect valve hemodynamic and valve reserve. 15 On the basis of the hemodynamic data, the present study demonstrated no change in left atrial pressures before and after creation of the double-orifice mitral valve, which supports the absence of mitral stenosis.…”
Section: Discussionsupporting
confidence: 48%
“…Clinically, others have shown that even with concomitant ring annuloplasty, the edge-to-edge technique does not cause mitral valve obstruction, either at baseline or during physical exercise, and does not affect valve hemodynamic and valve reserve. 15 On the basis of the hemodynamic data, the present study demonstrated no change in left atrial pressures before and after creation of the double-orifice mitral valve, which supports the absence of mitral stenosis.…”
Section: Discussionsupporting
confidence: 48%
“…Although structural and FSI models of the native MV exist (Votta et al, 2008;Kunzelman et al, 2007), the ETER has been previously modelled using structural-only (Avanzini, 2008;Dal Pan et al, 2005;Votta et al, 2002) or valveless fluid-only approaches (Redaelli et al, 2001), both of which have limitations. Structural-only models assume the haemodynamic pressure load is uniform over the surface of the valve, a factor which has been previously shown to affect valve dynamics (Lau et al, 2010).…”
Section: Finite Element Modelsmentioning
confidence: 99%
“…Fluid-only models (Redaelli et al, 2001) have studied the effect of the ETER by defining a fluid volume with single/double orifice/s representing the corrected valve geometry following ETER. The effects of a single orifice (uncorrected), double orifice (central leaflet correction) and an asymmetric single orifice (commissural leaflet correction) have been examined, with results indicating that the key factor affecting the transvalvular pressure drop is the total cross-sectional area of the repaired valve.…”
Section: Finite Element Modelsmentioning
confidence: 99%
“…Diastolic load was determined from the fluid-dynamic FEM model proposed by Redaelli et al (2001). This model hypothesises a constant blood flow rate across the valve Q (l/min), determining the diastolic pressure drop (Dp, mmHg) as a function of the effective orifice area (A, mm 2 ).…”
Section: Loadingmentioning
confidence: 99%